Exploring Metaverse Adoption Intentions among Nigerian Media Organisations - Inobemhe, Kelvin; Ja'afaru, Sharifatu; Anagu, Emmanuel (Journal of Techno-Social, 2025)
The Metaverse presents significant opportunities for transforming media practices and audience engagement, particularly in emerging markets like Nigeria. This study examines the willingness of Nigerian media houses to adopt Metaverse technologies by integrating insights from the Extended Unified Theory of Acceptance and Use of Metaverse Technology (UTAUMT). Through a survey of media professionals, key factors influencing adoption intention were identified, including performance expectancy, social influence, and facilitating conditions. Findings showed despite the technical and infrastructural issues encountered, Metaverse comes with critical opportunities that can be leveraged for dynamic advertising, virtual events and immersive storytelling. Theoretically, the study contributes to the systematisation of ideas in respect of the relevance of Metaverse especially in relations to adoption and acceptance technology. From a practical perspective, findings of the study can be relied upon to take decisions on adoption and use of Metaverse across industries. This study offers the need for strategic integration and makes case of addressing organisational barriers and cultural issues while efforts are made to foster innovation in fast-paced digitised Nigerian media landscape.